Neurodynamic Treatment Promotes Mechanical Pain Modulation in Sensory Neurons and Nerve Regeneration in Rats - Giacomo Carta; Benedetta Elena Fornasari; Federica Fregnan; Giulia Ronchi; Stefano De Zanet; Luisa Muratori; Giulia Nato; Marco Fogli; Giovanna Gambarotta; Stefano Geuna; Stefania Raimondo (Biomedicines, 2022)
Background: Somatic nerve injuries are a rising problem leading to disability associated with neuropathic pain commonly reported as mechanical allodynia (MA) and hyperalgesia. These symptoms are strongly dependent on specific processes in the dorsal root ganglia (DRG). Neurodynamic treatment (NDT), consisting of selective uniaxial nerve repeated tension protocols, effectively reduces pain and disability in neuropathic pain patients even though the biological mechanisms remain poorly characterized. We aimed to define, both in vivo and ex vivo, how NDT could promote nerve regeneration and modulate some processes in the DRG linked to MA and hyperalgesia. Methods: We examined in Wistar rats, after unilateral median and ulnar nerve crush, the therapeutic effects of NDT and the possible protective effects of NDT administered for 10 days before the injury. We adopted an ex vivo model of DRG organotypic explant subjected to NDT to explore the selective effects on DRG cells. Results: Behavioural tests, morphological and morphometrical analyses, and gene and protein expression analyses were performed, and these tests revealed that NDT promotes nerve regeneration processes, speeds up sensory motor recovery, and modulates mechanical pain by affecting, in the DRG, the expression of TACAN, a mechanosensitive receptor shared between humans and rats responsible for MA and hyperalgesia. The ex vivo experiments have shown that NDT increases neurite regrowth and confirmed the modulation of TACAN. Conclusions: The results obtained in this study on the biological and molecular mechanisms induced by NDT will allow the exploration, in future clinical trials, of its efficacy in different conditions of neuropathic pain.